IDENTIFYING VARIOUS FORMS OF LANGUAGE LEARNING ACTIVITIES IN TEACHING LANGUAGE SKILLS - Bozorova Muhabbat Abdurahmonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is about identifying various forms of language learning activities in teaching language skills and there are given some activities.